Internet addiction and its effects on psychological wellbeing among adolescents in the urban health and rural health training centre, Jaipur, Rajasthan, India - Kishan, Dev; Muraleedharan, Deepak; Vijayvergia, Bhawana (International Journal Of Community Medicine And Public Health, 2025)
Background: In 2023, there were almost 4.8 billion active internet users worldwide, equivalent to 62% of the global population. The majority of Indian youth comprising 85% of non–adult users, have access to smartphones. Most of them were online five hours a day and 80% admitted to using social media. Objective: To assess internet addiction prevalence among adolescents in UHTC and RHTC areas, evaluate varying usage levels, analyze their correlation and identify demographic factors (age, sex, socioeconomic status) influencing its impact on psychological well-being. Methods: A community based cross-sectional study of 200 adolescents from urban and rural areas was conducted via by simple random sampling from January to July 2023 at Sawai Man Singh Medical College, Jaipur to determine their internet usage patterns and psychological implications. We acquired the data from the subjects via the IAT- Internet Addiction Test and the GHQ-12 General Health Questionnaire-12. We took oral interviews of the subjects’ sociodemographic information and internet usage patterns. Results: A statistically significant difference in internet usage patterns was detected, as measured by the average internet Addiction Test (IAT) score. A difference was also observed in psychological health, as measured by the average General Health Questionnaire (GHQ) score. Additionally, there was a significant positive association between overall severity of internet use and poorer psychological health (GHQ-12 score). Conclusions: Our study highlights rural-urban disparities in internet usage and psychological health. It emphasizes the need for educational initiatives to promote responsible internet use and enhance mental well-being among youth.